Action at a distance: Long-distance rate adaptation in event perception. Issue 2 (February 2021) - Heffner, Christopher C; Newman, Rochelle S; Idsardi, William J
Viewers' perception of actions is coloured by the context in which those actions are found. An action that seems uncomfortably sudden in one context might seem expeditious in another. In this study, we examined the influence of one type of context: the rate at which an action is being performed. Based on parallel findings in other modalities, we anticipated that viewers would adapt to the rate at which actions were displayed at. Viewers watched a series of actions performed on a touchscreen that could end in actions that were ambiguous to their number (e.g., two separate "tap" actions versus a single "double tap" action) or identity (e.g., a "swipe" action versus a slower "drag"). In Experiment 1, the rate of actions themselves was manipulated; participants used the rate of the actions to distinguish between two similar, related actions. In Experiment 2, the rate of the actions that preceded the ambiguous one was sped up or slowed down. In line with our hypotheses, viewers perceived the identity of those final actions with reference to the rate of the preceding actions. This was true even in Experiment 3, when the action immediately before the ambiguous one was left unmodified. Ambiguous actions embedded in a fast context were seen as relatively long, while ambiguous actions embedded in a slow context were seen as relatively short. This shows that viewers adapt to the rate of actions when perceiving visual events.